Telaah Kritis Konsep Syariat, Tarekat, Hakikat dan Ma’rifat dalam Tasawuf - Ardiwisastra Mu’allim (Lembaga Pengembangan Kinerja Dosen, 2023)
Before proceeding to criticize the material of Shari'a, tariqa, essence and ma'rifat in the book Akidah Akhlak Madrasah Aliyah Class XI Ministry of Religion of the Republic of Indonesia 2020, it is better if the researcher first explains about the four dimensions of Sufism mentioned above by quoting some information from various sources. the majority of books written by the perpetrators of Sufism itself. This is to provide a broader picture and help understand criticism and its object. This is because the material contained in the book Akidah Akhlak Madrasah Aliyah Class XI of the Ministry of Religion of the Republic of Indonesia 2020 is very limited and only discusses the outer shell. While the researcher's criticism intends to open the eyes of the world of education from the impact of loading this material in textbooks.